(untitled) (American Journal of Research in Humanities and Social Sciences, 2025)
This study examines the Lebanese cultural role in the Arab Renaissance during the period between 1860 and 1914, through an analysis of the historical and social factors that contributed to the development of renaissance thought. The research focuses on three main axes: the historical and social context of Lebanon in the nineteenth century, the role of Lebanese journalism in disseminating enlightenment ideas, and the contributions of educational institutions and cultural associations in reinforcing Arab identity. The study highlights the influence of Lebanese journalism in promoting national and intellectual awareness and its connection to reformist movements across the Arab world. It also discusses the emergence of modern educational institutions and the spread of national schools, emphasizing their role in forming an educated class that played a vital part in the intellectual and political revival. Furthermore, the research explores the role of cultural associations in supporting education and spreading enlightenment thought, as well as the challenges they faced under Ottoman policies, culminating in the impact of World War I on Lebanon’s cultural and educational movement. The study concludes that the Lebanese cultural renaissance was the result of both internal and external dynamics, and it laid a foundational platform for intellectual and political movements in the Arab world, despite the obstacles encountered.